2016
DOI: 10.1002/2015gb005327
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of carbonate chemistry, production, and calcification of the Florida Reef Tract (2009–2010): Evidence for seasonal dissolution

Abstract: Ocean acidification is projected to lower the Ω ar of reefal waters by 0.3-0.4 units by the end of century, making it more difficult for calcifying organisms to secrete calcium carbonate while at the same time making the environment more favorable for abiotic and biotic dissolution of the reefal framework. There is great interest in being able to project the point in time when coral reefs will cross the tipping point between being net depositional to net erosional in terms of their carbonate budgets. Periodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
87
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 87 publications
(154 reference statements)
13
87
0
Order By: Relevance
“…Here, it appears that although the Bermuda reef system is dominated by net calcification, the reef system can switch to net dissolution seasonally. Similar seasonal net dissolution has been recently observed on the Florida Reef tract (Muehllehner et al, 2016).…”
Section: Does the Bermuda Reef Exhibit Seasonal Changes In Biogeochemsupporting
confidence: 86%
“…Here, it appears that although the Bermuda reef system is dominated by net calcification, the reef system can switch to net dissolution seasonally. Similar seasonal net dissolution has been recently observed on the Florida Reef tract (Muehllehner et al, 2016).…”
Section: Does the Bermuda Reef Exhibit Seasonal Changes In Biogeochemsupporting
confidence: 86%
“…The aragonite saturation state ( arag ) and pCO 2 are reported based on DIC-pH pairs, with dissociation constants K 1 and K 2 from Mehrbach et al (1973) refit by Dickson and Millero (1987) and KSO 4 from Dickson (1990). The TA and DIC values were normalized to salinity (by multiplying by a factor of 35/S, where S is the measured salinity value) to account for variations in TA and DIC along the reef flat driven by evaporation and/or precipitation (Friis et al, 2003) and are reported as nTA and nDIC as previously established in reef geochemical surveys (e.g., Suzuki and Kawahata, 2003;Yates et al, 2014;Muehllehner et al, 2016) where TA and DIC exhibit non-conservative behavior with respect to salinity. However, at the vent site, the TA and DIC data were not normalized to salinity given the contribution of TA and DIC from SGD.…”
Section: Samples For Dissolved Nutrients (Nhmentioning
confidence: 99%
“…The carbonate chemistry system is sensitive to changes in photosynthesis, respiration, calcification, and calcium carbonate (CaCO 3 ) dissolution, and can be characterized by measuring total alkalinity (TA), dissolved inorganic carbon (DIC), pH, pCO 2 , nutrients, salinity, and temperature. Analysis of these parameters yields valuable information on ratios of net community calcification and production, and can be used to identify biological and physical drivers of reef health and ecosystem function (Silverman et al, 2007;Shamberger et al, 2011;Lantz et al, 2014;Albright et al, 2015;Muehllehner et al, 2016;DeCarlo et al, 2017;Richardson et al, 2017;Cyronak et al, 2018). This is particularly important given growing concern that coastal and ocean acidification may shift reef ecosystems from calcification to dissolution by the middle to end of the century (Silverman et al, 2009;Andersson and Gledhill, 2013) with an overall reduction in calcification rates and increase in dissolution rates (Shamberger et al, 2011;Shaw et al, 2012;Bernstein et al, 2016) that can contribute to reef collapse (Yates et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies which have examined the effect of excess OM on coral reef sediment metabolism over longer timescales (months) have shown that, ultimately, GPP / R eventually shifts to net heterotrophy (e.g. Andersson, 2015;Yeakel et al, 2015;Muehllehner et al, 2016). This suggests that despite an initial OM-induced increase in GPP / R, the net long-term effect within reef sediments may be a preferentially heterotrophic recycling of nutrients released from organic matter degradation.…”
Section: Introductionmentioning
confidence: 99%